The Wnt receptor Frizzled-4 modulates ADAM13 metalloprotease activity - Abbruzzese, Genevieve; Gorny, Anne-Kathrin; Kaufmann, Lilian T.; Cousin, Hélène; Kleino, Iivari; Steinbeisser, Herbert; Alfandari, Dominique (Journal of cell science, 2015)
Skip to Next Section - Cranial neural crest (CNC) cells are a transient population of stem cells that originate at the border of the neural plate and the epidermis, and migrate ventrally to contribute to most of the facial structures including bones, cartilage, muscles and ganglia. ADAM13 is a cell surface metalloprotease that is essential for CNC cell migration. Here, we show in Xenopus laevis embryos that the Wnt receptor Fz4 binds to the cysteine-rich domain of ADAM13 and negatively regulates its proteolytic activity in vivo. Gain of Fz4 function inhibits CNC cell migration and can be rescued by gain of ADAM13 function. Loss of Fz4 function also inhibits CNC cell migration and induces a reduction of mature ADAM13, together with an increase in the ADAM13 cytoplasmic fragment that is known to translocate into the nucleus to regulate gene expression. We propose that Fz4 associates with ADAM13 during its transport to the plasma membrane to regulate its proteolytic activity.
Gesehen am 03.11.2020